Shameless : The Canine and the Feminine in Ancient Greece - Franco, Cristiana (Book collections on Project MUSE., 2015)
Cristiana Franco examines the long-standing association between women and dogs and their respective places in ancient Greek society, not only in fact, but also in the popular imagination. Franco's argument extends beyond the boundaries of classics and anthropology, forming a model of the sensitive work that can be done to better illuminate how deeply non-human animals are imbricated in human history. The English translation includes a methodological appendix by the author that will point the way toward future work in the emerging field of human-animal studies.